ANALISIS KAUSALITAS TRIPLE DEFICIT HYPOTHESIS DI INDONESIA - Lara Putri Arantika; Yeniwati Yeniwati; Mike Triani (Universitas Negeri Padang, 2018)
This study aims to determine and analyze the causal relationship of triple deficit hypotheis between budget deficit, current account deficit, and saving-investment gap in Indonesia by using Vector Autoregression (VAR) method. The type of this research is descriptive reseacrh, where the data used secondary data in the form of time series data from the year 2003:Q1-2016:Q4. The finding of this study indicate that budget deficit and current account deficit have one-way relationship, budget deficit and saving-investment gaphave one-way relationship and current account deficit and saving-investment gap not have causality or one-way relationship.